Culturally adapting psychotherapy for Asian heritage populations : an evidence-based approach - Hwang, Wei-Chin. (Cambridge, MA : Academic Press is an imprint of Elsevier, 2016)
Culturally Adapting Psychotherapy for Asian Heritage Populations: An Evidence-Based Approach provides insights on how research on psychotherapy, an area that is most often done on non-ethnic minority populations, can be related to minority clients. The book's author, Dr. Hwang, developed the first evidence based culturally adapted treatment for Asian populations which is comprehensively discussed in this book, including treatments for depression that are complemented with concrete examples throughout the book. In addition, the book further discusses how culturally adaptive techniques can be applied for treatment of other disorders in other ethnic populations.
Traditional and Indigenous Medicines, Spiritual Leaders, and Healing MethodsPatient or Client Feedback; CBOs and Community Leaders; Phase 2: Integrating Generated Information With Theory and Empirical and Clinical Knowledge; Phase 3: Reviewing the Initial Culturally Adapted Clinical Intervention With Stakeholders and Revising the Culturally Adapt ... ; Phase 4: Testing the Culturally Adapted Intervention; Phase 5: Synthesizing Knowledge Produced by the Earlier Phases and Finalizing the Culturally Adapted Intervention; References.
Online resource; title from PDF title page (EBSCO, viewed April 18, 2016).
Includes bibliographical references and index.
Keywords: Asian Americans -- Mental health; Psychotherapy -- Asian Americans; Counseling psychology; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Asian Americans -- Mental health; Counseling psychology; Electronic books